The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11999-008-0238-z
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction Technique Affects Femoral Tunnel Placement in ACL Reconstruction

Abstract: Grafts placed too anteriorly on the femur are reportedly a common cause of failure in anterior cruciate ligament reconstruction. Some studies suggest more anatomic femoral tunnel placement improves kinematics. The ability of the transtibial technique and a tibial tunnel-independent technique (placed transfemorally outside-in) to place the guide pin near the center of the femoral attachment of the anterior cruciate ligament was compared in 12 cadavers. After arthroscopic placement of the guide pins, the femur w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
143
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 48 publications
6
143
0
1
Order By: Relevance
“…1, C). These findings are consistent with prior cadaver studies that evaluated tunnel position in traditional transtibial anterior cruciate ligament reconstruction [5][6][7][8] . In those studies, the tunnels were drilled during arthroscopy or in an open fashion and were evaluated postoperatively during dissection.…”
Section: Source Of Fundingsupporting
confidence: 90%
“…1, C). These findings are consistent with prior cadaver studies that evaluated tunnel position in traditional transtibial anterior cruciate ligament reconstruction [5][6][7][8] . In those studies, the tunnels were drilled during arthroscopy or in an open fashion and were evaluated postoperatively during dissection.…”
Section: Source Of Fundingsupporting
confidence: 90%
“…Drilling can be undertaken through an accessory AM portal or with our TransLateral technique. 30 ACL footprint anatomy has been defined, 42 and identification of the mid-bundle position on the femur can be achieved with the direct measurement technique, which has been validated. 32 Biomechanical testing has shown that single-bundle anatomic positioning confers advantages over traditional graft placement, but further improvements may be obtained by double-bundle reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Kaseta et al [11], more anatomic placement of the femoral tunnel was achieved using the femoral footprint as a landmark than with the over-the-top positioning guide, which resulted in femoral tunnel placement that was typically too anterior.…”
Section: Discussionmentioning
confidence: 99%